2022
DOI: 10.1002/kjm2.12622
|View full text |Cite
|
Sign up to set email alerts
|

Elevated intramuscular adipose tissue content with a high Ishak fibrosis stage (>3) had a negative effect on liver regeneration in cirrhotic patients undergoing portal vein embolization

Abstract: This study investigated the relationship between body composition parameters and changes in future liver remnant volume (FLRV) in hepatocellular carcinoma (HCC) patients undergoing portal vein embolization (PVE) in preparation for right hepatectomy. This retrospective study enrolled 21 patients between May 2013 and October 2020. Body composition parameters, including skeletal muscle attenuation (SMA), skeletal muscle mass index (SMI), intramuscular adipose tissue content (IMAC), and visceral‐to‐subcutaneous ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Among the patients, 14 exhibited severe liver fibrosis (Ishak score 5 and 6). Previous studies have shown that the degree of liver fibrosis has a negative effect on liver regeneration in cirrhotic patients undergoing portal vein embolization (PVE) 20 , 21 . However, results for ALPPS patients have been controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Among the patients, 14 exhibited severe liver fibrosis (Ishak score 5 and 6). Previous studies have shown that the degree of liver fibrosis has a negative effect on liver regeneration in cirrhotic patients undergoing portal vein embolization (PVE) 20 , 21 . However, results for ALPPS patients have been controversial.…”
Section: Discussionmentioning
confidence: 99%